KOREA MERCHANDISE MARKETING STRATEGY IN GENERATION Z (Jurnal Ekonomi : Journal of Economic, 2022)
One of the merchandises that the current generation Z loves the most is merchandise that originated in Korea. Merchandise from Korea is dominating the merchandise market shifting its previous merchandise products originating in Western countries. This study aims to analyze the marketing strategy of Korean merchandise among the z-generation. The research approach uses a descriptive qualitative approach. Research data were obtained through tracing of various digital media and popular sites related to marketing of korean merchandise. Research results show that in addition to the factors of "Korean fever" with music and dramas, Korean merchandise sales strategies are effective through various social media platforms such as Line, Twitter, Instagram, Shopee, Lazada, Tokopedia. In order to increase the effectiveness of the sale of such medsos then the need for admin handle to serve orders is primarily Group Order (GO. With the presence of an admin handle then increases the intensity of communication with consumers and can effectively increase product sales.